2020
DOI: 10.48550/arxiv.2006.02451
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the AGN nature of two UV bright sources at z_spec~5.5 in the CANDELS fields: an update of the AGN space density at M1450~-22.5

A. Grazian,
E. Giallongo,
F. Fiore
et al.

Abstract: It is a widespread opinion that hydrogen reionization is mainly driven by primeval star-forming galaxies, with a minor role of high-z active galactic nuclei. Recent observations, however, challenge this notion, indicating a number of issues related to a galaxy-driven reionization scenario. We provide here an updated assessment of the space density of relatively faint (M 1450 ∼ −22.5) AGNs at z spec ∼ 5.5 in order to improve the estimate of the photo-ionization rate contribution from accreting super massive bla… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 140 publications
(285 reference statements)
1
6
0
Order By: Relevance
“…Therefore, we also compute an upper limit to reionization from AGN, by considering the high escape fraction suggested by Grazian et al (2018) for both unabsorbed and Compton-thin AGN (log N H < 24) at all redshifts and luminosity. Figure 4 shows that the A19-based UV photoionization rate for AGN with log N H < 24 (grey lines) agrees well with the Giallongo et al (2019) and Grazian et al (2020) UV LFs (blue and red points, respectively), both where AGN space densities Table 1. Radiative Efficiency (a) and Spin (b) XLF η kin η (c) Spin A19 (d) 0 0.34 +0.15 −0.16 (0.118 +0.024 −0.020 ) 0.998 +0.000 −0.018 (0.783 +0.096 −0.056 ) 0.15 0.30 +0.12 −0.15 (0.100 +0.021 −0.019 ) 0.9995 +0.0 −0.0012 (0.9832 +0.0039 −0.0034 ) U14 0 0.20 +0.18 −0.10 (0.068 +0.022 −0.023 ) 0.997 +0.000 −0.039 (0.28 +0.20 −0.15 ) 0.15 0.178 +0.162 −0.098 (0.059 +0.021 −0.023 ) 0.99961 +0.0 −0.00081 (0.9632 +0.0056 −0.0037 ) (a) Calculated for different XLFs and values of ρ SMBH .…”
Section: Contribution To Cosmic Reionizationmentioning
confidence: 52%
See 3 more Smart Citations
“…Therefore, we also compute an upper limit to reionization from AGN, by considering the high escape fraction suggested by Grazian et al (2018) for both unabsorbed and Compton-thin AGN (log N H < 24) at all redshifts and luminosity. Figure 4 shows that the A19-based UV photoionization rate for AGN with log N H < 24 (grey lines) agrees well with the Giallongo et al (2019) and Grazian et al (2020) UV LFs (blue and red points, respectively), both where AGN space densities Table 1. Radiative Efficiency (a) and Spin (b) XLF η kin η (c) Spin A19 (d) 0 0.34 +0.15 −0.16 (0.118 +0.024 −0.020 ) 0.998 +0.000 −0.018 (0.783 +0.096 −0.056 ) 0.15 0.30 +0.12 −0.15 (0.100 +0.021 −0.019 ) 0.9995 +0.0 −0.0012 (0.9832 +0.0039 −0.0034 ) U14 0 0.20 +0.18 −0.10 (0.068 +0.022 −0.023 ) 0.997 +0.000 −0.039 (0.28 +0.20 −0.15 ) 0.15 0.178 +0.162 −0.098 (0.059 +0.021 −0.023 ) 0.99961 +0.0 −0.00081 (0.9632 +0.0056 −0.0037 ) (a) Calculated for different XLFs and values of ρ SMBH .…”
Section: Contribution To Cosmic Reionizationmentioning
confidence: 52%
“…Their analysis of several AGN optical and UV LFs (Willott et al 2009(Willott et al , 2010McGreer et al 2013) indicate that quasar emissivity is too low to be a significant contributor to reionization, although at the time faint-end of the quasar luminosity function was rather uncertain. Recently, the faint-end has been updated by Giallongo et al (2019) and Grazian et al (2020), so we compare A19 XLF with these new high redshift quasar number densities as well as with the Bouwens et al (2015b) results. Mason et al (2019) derived a non-parametric form of total Ṅion (z) by combining constrains from optical depth, dark gap statistics, Lyα damping wings of quasars and ratio of Lyα emitters over Lyman break galaxies.…”
Section: Total Ultraviolet Emission and Contribution From Galaxiesmentioning
confidence: 83%
See 2 more Smart Citations
“…vealed a large number of faint quasars at high redshifts, supporting a significant contribution of quasars to the IGM ionizing background (Glikman et al 2011;Boutsia et al 2018;Grazian et al 2020). In particular, for Xray-selected quasars with M 1450 ≥ −22 mag, Giallongo et al (2019;hereafter G19) have suggested a substantial contribution of quasars ( 50%, depending on z) to the IGM ionizing background (see also Giallongo et al 2015).…”
Section: Introductionmentioning
confidence: 86%